THE EFFECTS OF AN EFL TEXTBOOK ON LEARNERS’ IDENTITY CONSTRUCTION - Neng Priyanti (Universitas Pelita Harapan, 2019)
It has been generally accepted that language learning, to some extent, affects identity construction and such a complex relationship has generated a considerable amount of research papers and literature. Few studies, however, have looked into and discussed how teaching media (e.g., language textbooks) contributes to learners’ identity construction particularly in the context of Indonesia. This study attempts to address this gap by analyzing an EFL textbook and then, grafting on several theoretical frameworks, discussing its contribution to the formation of learners’ identity. Its pedagogical implications are also discussed.